2012
DOI: 10.1016/j.rpor.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Non-closure of peritoneum after abdominal hysterectomy for uterine carcinoma does not increase late intestinal radiation morbidity

Abstract: Non-closure of the visceral peritoneum after hysterectomy for uterine corpus carcinoma does not increase the volume of the small intestine within the irradiated volume, with no consequent intestinal morbidity enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…A previous double blind randomized trial was performed to evaluate the intensity of post-caesarean pain between closure and nonclosure group reached hardly no difference in postoperative pain in both groups in successive cesareans. 11 Moreover, in the current research, there was a statistically significant difference between the closure and non-closure groups during hysterectomy regarding VAS after 12 hours and 24 hours with p value > 0.001.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…A previous double blind randomized trial was performed to evaluate the intensity of post-caesarean pain between closure and nonclosure group reached hardly no difference in postoperative pain in both groups in successive cesareans. 11 Moreover, in the current research, there was a statistically significant difference between the closure and non-closure groups during hysterectomy regarding VAS after 12 hours and 24 hours with p value > 0.001.…”
Section: Discussionsupporting
confidence: 44%
“…In a recent study, made by Igor Sirák et al, 11 on non-closure of peritoneum after abdominal hysterectomy for uterine carcinoma does not increase late intestinal radiation morbidity .Also, there is no subsequent intestinal morbidity enhancement in these patients. 12 In a recent study made by Wagdy M Amer, 12 they reported that visceral and parietal peritoneum in CS, the non-closure approach is recommended due to its much shorter operating time and lower postoperative pain score.…”
Section: Discussionmentioning
confidence: 93%